Surface structure formation in WE54 Mg alloy subjected to ultrafast laser texturing - Khadka, Indira (2016)
Pico- and femtosecond lasersurfacestructuring of WE54 Mg alloy was investigated in this paper. In particular, the effective response of rare earth elements during laser structuring and the surface structure formation mechanisms were studied. A 10 W picosecond laser, having a wavelength of 1064 nm, and a 1.5 W femtosecond laser, having a wavelength of 795 nm, were used to irradiate WE54 surface to change the surface morphology. A number of pulses varying from 100 to 1500 were applied to create a crater at single and multiple points on the WE54 alloy surface in an air medium. Taylor Hobson profilometer and energy dispersive x-ray spectroscopy (EDS) techniques were employed in order to analyze the modification in surface morphology and chemical composition, respectively. A crater depth around 1.1 μm was measured by the profilometer. It was observed that a compound of yttrium and neodymium was formed during the process of rapid thermalization, which is investigated by x-ray diffraction. The surface portion containing yttrium was converted into a white crystal-like structure as observed by optical and scanning electron microscope (SEM). The white color compound of rare earth element is turned into gray, then dark, and is finally ablated from the surface with increasing scanning number and number of laser pulses. The change in color represents the change in optical properties of WE54. SEM analysis also revealed that no cracks were present on the laser structuredsurface; hence, stress effect on the surface can be neglected. Explosive vaporization of the substrate was observed in pico- and femtosecond laserstructuring. The investigation on ultrafast laserstructuring suggests that the surface properties created by laser structuring of WE54 can be controlled if proper laser processing is applied.